Analysis of control policies and dynamic response of a Q-car 2-DOF semi active system - Ihsan, Sany Izan; Faris, Waleed Fekry; Ahmadian, Mehdi (IOS Press, 2008)
Several control policies of Q-car 2-DOF semiactive system, namely skyhook, groundhook and hybrid controls are presented. Their ride comfort, suspension displacement and road-holding performances are analyzed and compared with passive system. The analysis covers both transient and steady state responses in time domain and transmissibility response in frequency domain. The results show that the hybrid control policy yields better comfort than a passive suspension, without reducing the road-holding quality or increasing the suspension displacement for typical passenger cars. The hybrid control policy is also shown to be a better compromise between comfort, road-holding and suspension displacement than the skyhook and groundhook control policies.